Unravelling foodborne viruses from fish matrices: evaluation of its potential food safety hazard - Silva, Andreia Filipa Oliveira da (2022)
"Food safety has been a concern for all societies since the beginning of humanity. The severity and impacts of this problem have changed through the ages and are still diverse across regions, countries, and communities. Yet, there are some challenges common to all countries, that unfortunately are dealt in different ways. For instance, only a fraction of food safety-related cases are recognised, treated accordingly, reported to public health authorities and recorded in official disease statistics (WHO 2015). Certain chronic diseases, such as cancer, kidney or liver failure, resulting from contaminated food appear long after the ingestion of food, and the causal link is seldom made for each case (WHO 2015). This points to some of the challenges inherent in measuring the burden associated with food safety and its toll on lives and economies (WHO 2015). (...)"